Effectiveness of Developing a STAD Model Integrated into Group Work Projects to Enhance Students’ Writing Skills - Karnedi, Karnedi (Universitas Pattimura, 2025)
This study aims to analyze and characterize the effectiveness of developing the Student Teams Achievement Division (STAD) model integrated with group work projects to improve students’ writing skills. A mixed-method approach, combining qualitative and quantitative methods, was employed in this research. The study utilized a pretest-posttest design for both control and experimental classes. The participants were fifth-semester English Education students at the Faculty of Teacher Training and Education (FKIP), Lancang Kuning University, with samples drawn from two classes: Regular A and Regular B. Writing tests served as the primary instrument for data collection. The STAD model integrated with group work projects was implemented in Regular A as the experimental class, while the conventional teaching method was applied in Regular B as the control class. The findings revealed that in the business letter writing test, the experimental class scored an average of 76.13, indicating a good quality rating, whereas the control class scored an average of 67.22, with some ideas and supporting evidence lacking. From the first to the sixth meeting, the experimental class demonstrated significant improvement in their business letter writing performance. The students showed an enhanced ability to provide the required information, respond to questions, and include additional details when prompted. They were trained to adhere to proper writing mechanics and to produce writing that is clear, vivid, precise, and specific. The novelty of this research lies in integrating the STAD model with group work projects, which proved effective in improving students’ writing skills, particularly in the context of business letter writing. This study recommends applying similar models in diverse learning contexts to foster broader writing skills development, thereby contributing to advancements in educational practices within the social and humanities fields.